2016
DOI: 10.1016/j.ophtha.2016.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Anti-Vascular Endothelial Growth Factor Therapies for AMD Did Not Raise Risk of Myocardial Infarction, Stroke, and Death

Abstract: Purpose To assess the effect of availability of anti-VEGF therapy on mortality and hospitalizations for stroke and acute myocardial infarction (AMI) over a 5-year follow-up period in US Medicare beneficiaries newly diagnosed with exudative age-related macular degeneration (AMD) in 2006 compared to control groups consisting of beneficiaries newly diagnosed with exudative AMD at a time when anti-VEGF therapy was not possible and with a control group of beneficiaries newly diagnosed with non-exudative AMD. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In Taiwan, patients with nAMD might have received treatment with anti‐VEGF injections during their disease course since 2006. Although this treatment was reported to be safe in most studies, cerebral hemorrhage after the injection has been reported . This adverse effect might be one reason why patients with nAMD have a higher risk of developing hemorrhagic strokes.…”
Section: Discussionmentioning
confidence: 98%
“…In Taiwan, patients with nAMD might have received treatment with anti‐VEGF injections during their disease course since 2006. Although this treatment was reported to be safe in most studies, cerebral hemorrhage after the injection has been reported . This adverse effect might be one reason why patients with nAMD have a higher risk of developing hemorrhagic strokes.…”
Section: Discussionmentioning
confidence: 98%
“…There is strong evidence from randomized controlled trials and studies based on observational data that patients who adhere to evidence-based treatment recommendations for diabetes care experience better health outcomes (e.g., Chen et al 2015). A high degree of adherence leads to better glycemic control, fewer complications (e.g., blindness, leg amputations), and lower risks for all-cause hospitalization and all-cause mortality (Ho et al 2006; Yashkin et al 2016). However, a substantial proportion of persons who are diagnosed with diabetes do not adhere to guidelines for diabetes care, despite the potentially large benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses, combining the data from various randomized controlled trials, yielded an overall low thromboembolic event rate [16] . In addition, a recent retrospective cohort analysis of United States Medicare beneficiaries with AMD did not show an increased risk for acute myocardial infraction, stroke, or all-cause mortality comparing study cohorts prior and after the introduction of anti-VEGF agents as standard of care for neovascular AMD in 2006 [53] . 214 The SAVE-AMD study was stopped due to safety concerns, and, therefore, limited the power of the secondary ophthalmological outcomes.…”
Section: Discussionmentioning
confidence: 99%